Influência das técnicas de mínima quantidade de lubrificante, refrigeração otimizada e refrigeração convencional na qualidade de peças produzidas com aços endurecidos no processo de retificação - de Sampaio Alves, Manoel Cléber [UNESP]; Bianchi, Eduardo Carlos [UNESP]; de Aguiar, Paulo Roberto [UNESP] (My University, 2010)
The influence of minimum lubrication, optimized and conventional cooling at different flows and application rates of cutting fluids on the quality of hardened-steel pieces produced by external cylindrical plunge grinding with super-abrasive grinding wheels with low CBN concentrations was verified. The analysis of the quality of the pieces was performed through the assessment of the behavior of the specific energy of the grinding, roughness, roundness deviation, and the generated residual stress. By analyzing of the application ways and of the several flows and application rates of the cutting fluid, one could encounter lubrication/cooling conditions that enable the reduction in cutting fluid volume, reduction in grinding time without compromising the dimensional parameters (superficial finishing, surface integrity). Regarding the different applications of cutting fluids, it could be noted the optimized application for higher velocities has presented the best performance, demonstrating the effectiveness of the new concept of nozzle utilized.
Influence of the methods for minimum amount of lubrication, optimized cooling and conventional cooling in the quality of parts produced with hardened steel in grinding processes
Keywords: CBN grinding wheel; Conventional cooling; Grinding process; Minimum quantity of lubrication; Optimized cooling